2011
DOI: 10.1093/jxb/erq350
|View full text |Cite
|
Sign up to set email alerts
|

Root elongation, water stress, and mechanical impedance: a review of limiting stresses and beneficial root tip traits

Abstract: Root elongation in drying soil is generally limited by a combination of mechanical impedance and water stress. Relationships between root elongation rate, water stress (matric potential), and mechanical impedance (penetration resistance) are reviewed, detailing the interactions between these closely related stresses. Root elongation is typically halved in repacked soils with penetrometer resistances >0.8-2 MPa, in the absence of water stress. Root elongation is halved by matric potentials drier than about -0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
615
3
45

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 874 publications
(684 citation statements)
references
References 63 publications
21
615
3
45
Order By: Relevance
“…For the March sowing, the water limitation was greater, regardless of the level of soil compaction and phenological phase, in accordance with Bengough et al (2011) andBetioli Júnior et al (2012). It was observed that the soil compaction brought about by T 7 promoted water conditions (Fwithin) for vegetative growth of sorghum sown in January and February similar to that sown in March when the soil was in ideal structural conditions (Table 2).…”
Section: Monitoring Of the Soil Water Content According To The Llwr Csupporting
confidence: 60%
“…For the March sowing, the water limitation was greater, regardless of the level of soil compaction and phenological phase, in accordance with Bengough et al (2011) andBetioli Júnior et al (2012). It was observed that the soil compaction brought about by T 7 promoted water conditions (Fwithin) for vegetative growth of sorghum sown in January and February similar to that sown in March when the soil was in ideal structural conditions (Table 2).…”
Section: Monitoring Of the Soil Water Content According To The Llwr Csupporting
confidence: 60%
“…Under limited water and/or nutrient availability, the development of an extensive root system is a key determinant of crop yield (Bengough et al, 2011). To penetrate soil, an individual root must either follow the path of an existing pore network (White and Kirkegaard, 2010), or displace soil material by a combination of rigidbody movement, shear and compression (Bengough et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Other work has demonstrated that compacted soil layers may limit water movement, root penetration and therefore, plant water uptake (Bennie 1996;Bengough et al 2011). In such soil conditions tree roots play an important role in facilitating water flow and crop root penetration (Nair 1984;Van Noordwijk et al 1996).…”
Section: Introductionmentioning
confidence: 99%